Response of Grape and Wine Phenolic Composition in Vitis vinifera L. cv. Merlot to Variation in Grapevine Water Status - Bindon, K.; Myburgh, P.; Oberholster, A.; Roux, K.; du Toit, C. (South African Journal of Enology and Viticulture, 2011)
Grape and wine phenolic composition was monitored over two consecutive seasons in Vitis vinifera cv. Merlot following application of irrigation treatments that produced seasonal average stem water potentials ranging between -0.7 MPa and -1.4 MPa. Fresh weight of berries was significantly reduced in response to water deficit, primarily due to decreases in pericarp weight. Increases in the concentration of grape anthocyanins and flavonols in response to water deficit were found when expressed per unit grape berry fresh weight. Skin-derived tannin concentration in grape berries was not affected by the irrigation treatments. The concentration of grapederived phenolics was monitored during five days of fermentation in a small-lot winemaking experiment. During fermentation, the concentration of anthocyanins and flavonols in wine were highest in the non-irrigated and lowfrequency- irrigated treatments, which was reflected in changes in the wine colour of ferments. Finished wines from non-irrigated and low frequency irrigated grapevines showed increases in bisulphite-resistant pigments when compared with those irrigated at a high frequency, but differences in phenolic composition were minor. Increases in bisulphite-resistant pigments were associated with increases in vitisin A and polymeric pigment in the first and second seasons of the study respectively. Ageing of wines for an 18-month period increased bisulphite-resistant pigments, and treatment differences in wine colour density were enhanced, such that increases in both parameters were associated with the non-irrigated and low-frequency-irrigated treatments.